One-Step Hydrothermal Synthesis of Precious Metal-Doped Titanium DioxideGraphene Oxide Composites for Photocatalytic Conversion of CO2 to Ethanol - Napat Lertthanaphol; Natpichan Pienutsa; Kittapas Chusri; Thirawit Sornsuchat; Prowpatchara Chanthara; Panpailin Seeharaj; Pattaraporn Kim-Lohsoontorn; Sira Srinives (My University, 2021)
We utilized a one-step hydrothermal process for the synthesis of precious metal-doped titanium dioxide (TiO2)/graphene oxide (GO) composites. The metal-doped TiO2/GO composites, including silver-TiO2/GO (Ag-TiO2/GO), palladium-TiO2/GO (Pd-TiO2/GO), and copper-TiO2/GO (Cu-TiO2/GO), were synthesized by mixing a metal precursor, titanium butoxide, and graphene oxide in a water-ethanol mixture in an autoclave hydrothermal reactor. The photocatalytic performance of the composites was tested in the photoreduction of carbon dioxide (CO2) to ethanol. Ag-TiO2/GO, Pd-TiO2/GO, and Cu-TiO2/GO exhibited an ethanol production rate of 109, 125, and 233 μmol/gcat h, respectively. The outstanding performances of Cu-TiO2/GO can be attributed to a combined effect of key parameters, including optical band gap, crystallite size, and BET surface area.
Keywords: Titanium Dioxide; Autoclave; Hydrothermal Synthesis; Advanced Photocatalysis Techniques